Public Relations Leadership in Corporate Social Responsibility - Benn, Suzanne (Journal of business ethics, 2010)
Many of the negative connotations of corporate social responsibility (CSR) are linked to its perceived role as a public relations exercise. Following on calls for more positive engagement by public relations professionals in organisational strategic planning and given the rapidly increasing interest in CSR as a business strategy, this article addresses the question of how the theory and practice of public relations can provide direction and support for CSR. To this end, this article explores leadership styles and motivations of a sample of corporate leaders from prominent Australian-based corporations in relation to their chosen CSR activities to examine the current position of, and potential for, professional communicators’ impact in shaping CSR-driven policies at a strategic level. We find that while public relations theory has evolved, many leaders still see public relations professionals only as a source of positive publicity. Our findings suggest that the model of distributive leadership has more relevance to an emerging idea of public relations involvement in CSR than more traditional understandings of leadership. We conclude that the public relations profession needs to develop a greater understanding of senior management approaches to the development and dissemination of CSR activities to support organisational leadership as it currently operates with respect to CSR.